2014
DOI: 10.1172/jci76357
|View full text |Cite
|
Sign up to set email alerts
|

LMP1-deficient Epstein-Barr virus mutant requires T cells for lymphomagenesis

Abstract: formation comparison, the P value was calculated using a 2-tailed Fisher exact test. For viral load comparison, the P value was calculated using the Wilcoxon rank-sum test. A P value less than 0.05 was considered significant.Study approval. All animal experiments were approved by the University of Wisconsin-Madison IACUC and conducted in accordance with the NIH Guide for the Care and Use of Laboratory Animals. For human AIDS-related lymphomas, cases were collected from the Department of Pathology and Laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(100 citation statements)
references
References 51 publications
5
94
1
Order By: Relevance
“…The ligation of CD40 on B cells with its counter structure on T cells (CD154) elicits bi-directional signaling that is important for B cell activation and differentiation; antibody isotype switch also depends on CD40-CD154 interaction. In EBV-infected B cells the major oncoprotein LMP1 mimics constitutively activated CD40, but recent data suggest that activation signals can still be relayed through CD40 (Ma et al, 2015). In agreement, we observed that incubation of EBV-infected marmoset B cells with a stimulatory anti-CD40 mAb enhances IgG production (own unpublished observation).…”
Section: Treatments Targeting B Cellssupporting
confidence: 84%
“…The ligation of CD40 on B cells with its counter structure on T cells (CD154) elicits bi-directional signaling that is important for B cell activation and differentiation; antibody isotype switch also depends on CD40-CD154 interaction. In EBV-infected B cells the major oncoprotein LMP1 mimics constitutively activated CD40, but recent data suggest that activation signals can still be relayed through CD40 (Ma et al, 2015). In agreement, we observed that incubation of EBV-infected marmoset B cells with a stimulatory anti-CD40 mAb enhances IgG production (own unpublished observation).…”
Section: Treatments Targeting B Cellssupporting
confidence: 84%
“…Using this model, we recently showed that LMP1 is unexpectedly dispensable for EBV-induced lymphoma formation, since CD40L-expressing human CD4 T cells can partially substitute for LMP1 (38). Our results here suggest that neither LMP1 nor LMP2A is absolutely required for EBV-induced lymphomas in this model, even when both proteins are simultaneously deleted.…”
mentioning
confidence: 56%
“…To induce the formation of human B cell lymphomas in vivo, we briefly incubated human umbilical cord blood mononuclear cells (CBMCs) with EBV in vitro to allow viral attachment to the B cells, and then injected the human cells intraperitoneally into NSG mice (34). Using this protocol, typically about 90% of the mice develop tumors that result in mortality within 5 weeks ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…EBV is a human-specific γ-herpesvirus that is associated with several types of human B cell lymphoma, including Burkitt lymphoma, Hodgkin lymphoma, diffuse large B cell lymphoma, and posttransplant lymphoproliferative disease (33). A key feature of our model system is that neoplastic transformation of the human B cells occurs in the presence of autologous human T lymphocytes (34). Importantly, the autologous T cells are held in check by PD-1 and CTLA-4, which limit their ability to control the B lymphomas (35).…”
Section: Introductionmentioning
confidence: 99%